On the issue of improving the organization of the athletes training system - Приходько, Володимир; Ткачов, Сергій (Slobozhanskyi Herald of Science and Sport, 2019)
Volodymyr Prykhodko & Serhii Tkachov Purpose: on the basis of the analysis of the professional opinion of highly qualified coaches to summarize ways to improve the organization of the system of training athletes. Material & Methods: literature review; expert survey method of questioning; generalization and systematization of the data, methods of mathematical statistics. The study involved 18 honored coaches of Ukraine, who were interviewed by questioning. Results: As a result of the survey, leading coaches noted that in order to improve the organization of the athletes training system in Ukraine, it is necessary to ensure: raising the level of professional skills of coaches, raising the prestige of the coaching profession, encouraging coaches to productive activities to ensure the training of high-class athletes; development of the concept, strategy and schedule of reform for each individual sport; conducting internships for coaching staff abroad in countries where a particular sport has reached high development and recognition in the international arena; quality material and technical base and effective scientific and methodological support of sports activities; the use of continuous medical and biological control and medical and biological support; studying the competitive activity data of an athlete using a comparative analysis of video materials of performances of the best amateur athletes and professionals from the end of the twentieth century to the present day. Conclusions: strategy to solve this problem may be an approach based on a purely theoretical level with subsequent testing of the path produced, or a combination of existing developments with practical recommendations from experienced and reputable trainers and the creation on this basis of a more optimal solution to improve the organization of the modern system of training athletes.